Pola komunikasi orang tua dalam komunitas pushbike SBB Sumedang dalam mendukung kepercayaan diri anak - Firmansyah; Annisa Husnusyifa; Resty Mustika Pratiwi; Haryadi Mujianto (Universitas Garut, 2026)
Abstract This study aims to examine the patterns of parental communication within the SBB Sumedang pushbike community and their contribution to the development of self-confidence in early childhood. Pushbike activities not only help develop children's motor skills but also function as a social interaction space involving parents, children, and community members. This research employs a qualitative approach using a descriptive-interpretative method. The research subjects consisted of eight parents selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation in the form of photographs, videos, and digital communication within the community. Data analysis was conducted through data reduction, data display, and conclusion drawing using thematic analysis. The results indicate that parental communication patterns are supportive, participatory, and oriented toward the child's learning process. Affirmative verbal communication, calming nonverbal communication, and consistent emotional presence play important roles in fostering children's courage, independence, and social abilities. Parents interpret courage as the child's willingness to try, failure as part of the learning process, and success as the ability to complete training activities. The pushbike community functions as a social learning space for parents, shaping communication norms that support children's psychosocial development. These findings emphasize that supportive parental communication patterns within children's sports communities can serve as an important medium in shaping early childhood self-concept and self-confidence. Keywords: Parental communication; children's sports community; pushbike; child self-confidence; family communication. Abstrak Penelitian ini bertujuan untuk mengkaji pola komunikasi orang tua dalam komunitas pushbike SBB Sumedang dan kontribusinya terhadap pembentukan kepercayaan diri anak usia dini. Aktivitas pushbike tidak hanya melatih keterampilan motorik anak, tetapi juga menjadi ruang interaksi sosial antara orang tua, anak, dan anggota komunitas. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif-interpretatif. Subjek penelitian adalah delapan orang tua yang dipilih melalui purposive sampling, dengan data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi berupa foto, video, serta komunikasi digital komunitas. Analisis data dilakukan melalui reduksi, penyajian, dan penarikan kesimpulan menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa pola komunikasi orang tua bersifat suportif, partisipatif, dan berorientasi pada proses belajar anak. Komunikasi verbal afirmatif, komunikasi nonverbal yang menenangkan, serta kehadiran emosional konsisten, berperan penting dalam membangun keberanian, kemandirian, dan kemampuan sosial anak. Orang tua memaknai keberanian sebagai kemauan anak untuk mencoba, kegagalan sebagai bagian dari proses belajar, dan keberhasilan sebagai kemampuan menyelesaikan latihan. Komunitas pushbike berfungsi sebagai ruang pembelajaran sosial bagi orang tua, membentuk norma komunikasi yang mendukung perkembangan psikososial anak. Temuan ini menegaskan bahwa pola komunikasi orang tua yang suportif dalam komunitas olahraga anak dapat menjadi medium penting dalam membentuk konsep diri dan kepercayaan diri anak usia dini. Kata-kata kunci: Komunikasi orang tua; komunitas olahraga anak; pushbike; kepercayaan diri anak; komunikasi keluarga.